Parental Employment, School Climate, and Children's Academic and Social Development - SCHMITT, Neal (Institutional Knowledge at Singapore Management University, 1999)
Longitudinal data were used to examine the effects of parental employment status and school climate on children's academic and social development. Hierarchical regression, analyses of covariance, and latent growth modeling were used to assess various aspects of change as a function of work status and school climate with family income and education as control variables. Parental employment was associated with positive changes in social and academic progress even after controlling for prior developmental level, climate, and family income although effects were small and complex. School climate had minimal effect on the outcome variables. Income and education were related to various school outcomes. (PsycINFO Database Record (c) 2008 APA, all rights reserved). (from the journal abstract)